Subsurface Structural Characterization as Deduced from High-Resolution Aeromagnetic Data over The Confluence Zones in Central, Nigeria - Emmanuel Agada Anthony; Othniel Kamfani Likkason; Abubakar Sadiq Maigari; Sani Ali; Adamu Abubakar (MO.RI Publishing, 2023)
This study aimed to delineate the intrusion body that controls the structural setting and formation around the river Niger-Benue confluence zone with particular attention to its solid mineral potentials, this is achieved in mapping subsurface structural features through the analysis of recent high-resolution aeromagnetic (HRAM) data-sets with the purpose of examining their effects on geological structures that characterize the confluence zones from the study area. To obtain the necessary reduction in geomagnetic variation, measurements of regional gradients and time variation were used. After applying the reduction to the magnetic equator (RTE) to the corrected magnetic data that was obtained from the Nigerian Geological Survey Agency, NGSA, it was possible to determine the regional expansions of subsurface structural units for both qualitative and quantitative interpretations. In addition, the edge detection method is used to depict the structures and buried subsurface anomalies. Different handling processes were applied to the (HRAM) data, such as local wavenumber (SPI), power spectrum analysis, and Euler and Werner deconvolution analysis. The RTE magnetic anomaly caused by local structures and anomalous body delineated six sub-basins with low amplitude response, which agrees with the total gradient anomaly (analytic signal) and tilt of angle derivative that clearly outlined and characterize edges of lithostratigraphic of Niger-Benue river confluence zones. The sub-basin delineated are the southern Bida basin and northern Anambra basin. The source parameter imagings as well as the Euler and Werner deconvolution were used to delineate major subsurface structures and determine their source depth. Results showed that the area was affected by different lineament trending NE-SW, E-W, and S-E trends. Directional analysis indicates that the dominant trend agrees with the regional fault orientations. The estimated depth to the top of the lineaments on average varies from 0.3 km to 4.6 km and it is relatively deeper in the basins compared to the surrounding areas giving clues to the amount of sediment infill. A 2D forward model showed a sedimentary thickness ranging from 1 to 7 km, and this estimated depth is consistent with the average of 3.5 km proposed by previous researchers.